Partnering awareness in the Malaysian construction industry: A study on consultant engineers - Abdul Nifa, Faizatul Akmar; Ahmed, Vian; Abdul Rahim, Syukran (2015)
The traditional procurement system which is applied through the formation of temporary organizations has led to the segmented approach in construction projects delivery in the Malaysian construction industry.Consequently, in dealing with these issues, the Malaysian Construction Industry Development Board (CIDB) has identified and recommended partnering as a method to overcome the problems in the construction industry. Partnering is believed to be a viable approach to integrate the construction industry and construction project implementation, as well as creating conducive environment for innovations. The awareness of the consultants towards partnering is crucial as they are at a pivotal stage of introducing innovation in construction projects.This paper aims to explore the awareness of consultants towards partnering in the Malaysian construction industry through the use of qualitative methods.Findings indicate that although the consultant in Malaysia are positive towards partnering, there exists some hesitation in fully engaging in partnering ventures due to dissimilarities in organizational culture among firms in the partnering team.